Food Waste in Food Supply Chain: a study at retailer-consumer level of supply chain in the United Kingdom and India - KALYASHANTHARAJ, CHETHAN KUMAR (2011)
The aim of this research study is to identify the main causes of food waste in retailer-consumer interaction in the United Kingdom and India. Also to identify and suggest some solutions for the food waste at this level of food supply chain. There were around 30 people participated in the interview both in the UK and India to give share their knowledge and perception about the food waste. The primary objective of the research was to find out the main reasons of waste for some selected food items under three categories in the United Kingdom and India. Also to find out some existing solutions for the food waste. In order to achieve our goals I collected and analysed literatures which acted as secondary data for the research. To get the primary data I conducted interviews with the retailers and consumers in both the countries. In the later part I analysed the data obtained through interviews and based on the analysis I derived some important findings. The results I derived from our analysis and findings section were concluded in the final section.